2016
DOI: 10.3928/23258160-20160126-02
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Diabetic Macular Edema From Capillary Nonperfusion Using Optical Coherence Tomography Angiography

Abstract: The cystoid spaces in DME can be differentiated from capillary nonperfusion using OCTA. OCTA may help to guide treatment decisions in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 16 publications
2
60
0
1
Order By: Relevance
“…We speculate that this difference may be related to the presence of cystoid changes, which appear as areas of no-flow and are included in the nonperfusion computation. Such an effect has been demonstrated by de Carlo et al 28 However, if the vessels are simply displaced by the cysts and not actually lost, creating a thicker en face slab that includes the entire cyst and surrounding tissue may allow this question to be explored further.…”
Section: Discussionmentioning
confidence: 87%
“…We speculate that this difference may be related to the presence of cystoid changes, which appear as areas of no-flow and are included in the nonperfusion computation. Such an effect has been demonstrated by de Carlo et al 28 However, if the vessels are simply displaced by the cysts and not actually lost, creating a thicker en face slab that includes the entire cyst and surrounding tissue may allow this question to be explored further.…”
Section: Discussionmentioning
confidence: 87%
“…Suzuki et al 28 have reported decreased nonperfusion after anti-VEGF therapy in patients with RVO. de Carlo et al 39 also have reported the reappearance of retinal microvasculature after anti-VEGF treatment in the areas previously shown to have flow voids due to intraretinal fluid in diabetic macular edema (DME). They speculated that either the vessels that were poorly perfused prior to treatment, were re-perfused after an anti-VEGF treatment or the retinal vessels displaced or masked by the cystoid spaces reappeared after fluid resolution.…”
Section: Discussionmentioning
confidence: 97%
“…Diabetic macular edema (DME), the leading cause of vision loss in patients with DR, is visualized in en face OCTA as areas completely devoid of flow signal with smooth borders that do not follow the surrounding vessels (de Carlo, et al, 2016b, Matsunaga, et al, 2015). Eyes with DR and DME have increased FAZ and reduced vessel density in OCTA compared to those with DR without DME (Di et al, 2016, Kim et al, 2016).…”
Section: 6 Diabetic Macular Edema and Microaneurysmsmentioning
confidence: 99%